Corruption and Good Governance: An Analysis of ASEAN's E-Governance Experience - Rubasundram, Geetha A.; Rasiah, Rajah (ISEAS - Yusof Ishak Institute, 2019)
Since its formation in 1967, the Association of Southeast Asian Nations (ASEAN) has progressed to become an economic powerhouse. From a loosely formed grouping in the 1960s, its members have since undergone massive integration. A key motive of the Association is to transfer government and public services onto a technology platform, termed e-government. An important concern is whether e-governance can reduce corruption and stimulate sustainable development. Using traditional governance measures and e-governance indices, this paper analyses the state of governance and corruption in ASEAN. While the deepening of e-governance - via government and public participation - has raised the potential for improving good governance practices, that in itself can be counterproductive as socioeconomic agents could broaden corrupt practices by appropriating its public-good-like characteristics. Hence, ASEAN governments have to implement changes in their communications strategies and feedback mechanisms, remove barriers blocking the spread and use of information technology, and promote a collaborative environment with civil society organizations, while considering the use of the "carrot and stick" approach to improve good governance. © 2019 ISEAS - Yusof Ishak Institute.